Effect of novel sucrose based polyfunctional monomer on physico-mechanical and electrical properties of irradiated EPDM. (December 2021) - Abdel-Hakim, A.; El-Gamal, A.A.; EL-Zayat, Mai M.; Sadek, A.M.
Abstract: In this work a novel sucrose based polyfunctional monomer (SPF) was prepared and evaluated as a co-agent in the radiation crosslinking of Ethylene propylene diene methylene linkage rubber (EPDM). The incroporation of SPF boosted the crosslink density which is reflected postively on the gel content and swelling resistance of irradiated EPDM. The mechnical properties of EPDM enhanced as the SPF content increased where the highst tensile strength and elastic modulus were recorded for EPDM which contains 5 phr of SPF. In addition, a decrease in the dielectric constant and an increase in the electrical resistivity of EPDM were observed as SPF content increases. The thermal stability of EPDM was improved after the addition of SPF, especially at temeperature lower than 400 °C. Highlights: Novel sucrose based polyfunctional monomer (SPF) was prepared. Addition of SPF to irradiated EPDM improved the mechanical properties. The improvement in tensile strength was up to 161.35% compared to neat EPDM. Addition of SPF improved the electrical resistivity and thermal stability of EPDM.